Design in silico de catalisadores homogêneos contendo Ru e Rh para tecnologias de líquidos orgânicos carregadores de hidrogênio (LOHC) baseadas em compostos N-heterocíclicos - Izquierdo Soto, Rodolfo Enrique (Universidade Estadual Paulista (Unesp), 2025)
O projeto "In Silico Design of Homogeneous Catalysts Containing Ru and Rh for Organic Hydrogen Carrier Liquid (LOHC) Technologies Based on N-Heterocyclic Compounds" teve como foco o desenvolvimento de metodologias de DFT para investigar os mecanismos de reação da hidrogenação da quinolina utilizando catalisadores homogêneos à base de Ru, Rh, Os e Ir. Os resultados revelaram uma forte correlação entre determinados descritores derivados de DFT e as atividades catalíticas dos candidatos mais promissores. Como resultado direto, dois artigos foram publicados em ACS Omega e Catalysis Today em 2025. Infelizmente, não foi possível a renovação da bolsa de pós-doutorado para o período de 2025–2026.

The project "In Silico Design of Homogeneous Catalysts Containing Ru and Rh for Organic Hydrogen Carrier Liquid (LOHC) Technologies Based on N-Heterocyclic Compounds" focused on developing DFT methodologies to investigate the reaction mechanisms of quinoline hydrogenation using homogeneous catalysts based on Ru, Rh, Os, and Ir. The results revealed a strong correlation between selected DFT-based descriptors and the catalytic activities of the most promising candidates. As a direct outcome, two research articles were published in ACS Omega and Catalysis Today in 2025. Unfortunately, the postdoctoral fellowship renewal for the 2025–2026 period was not achieved.
In Silico Design of homogeneous catalysts containing Ru and Rh for organic hydrogen carrier liquid (LOHC) technologies based on N- heterocyclic compounds
O relatório contém material anexado relevante
Keywords: Homogeneous catalysts; Organic hydrogen carrier liquid (LOHC); DFT; Quinoline